Предмет: Математика,
автор: Дино43
решите уравнение
1) (2 + х) × 3,1 = -12,4
2)(1,2 + х) × (-5) = 4
Ответы
Автор ответа:
0
1)6,2+3,1x=-12,4
3,1x=-12,4-6,2
3,1x=-18,6
x=-18,6÷3,1
x=-6
2)-6-5x=4
-5x=4+6
-5x=10
x=10÷(-5)
x=-2
3,1x=-12,4-6,2
3,1x=-18,6
x=-18,6÷3,1
x=-6
2)-6-5x=4
-5x=4+6
-5x=10
x=10÷(-5)
x=-2
Автор ответа:
0
1)(2+х)*3,1=-12,4
2+х=-12,4:3,1
2+х=-124:31
2+х=-4
х=-4-2
х=-6
Ответ: 1)х=-6
2)(1,2+х)*(-5)=4
1,2+х=4:(-5)
1,2+х=-4/5
1,2+х=-0,8
х=-0,8-1,2
х=-2
Ответ: х=-2
2+х=-12,4:3,1
2+х=-124:31
2+х=-4
х=-4-2
х=-6
Ответ: 1)х=-6
2)(1,2+х)*(-5)=4
1,2+х=4:(-5)
1,2+х=-4/5
1,2+х=-0,8
х=-0,8-1,2
х=-2
Ответ: х=-2
Похожие вопросы
Предмет: Русский язык,
автор: kek305563
Предмет: Русский язык,
автор: vi9167777
Предмет: Геометрия,
автор: baukaauezov1985
Предмет: Алгебра,
автор: Аноним
Предмет: Алгебра,
автор: Аноним